Limite superior da retenção da água no solo: método de campo e método de estimativa - Vielmo, Alexandro Luiz (2008)
The superior limit of water retention in soil, also known as field capacity, still is motive of discussion and research inside the academic community. This happens because the variability of soils determines the alternation of results obtained by all methods that were performed. The need of accuracy, quickness of results, and test cost are the factors that point which method should be used. The recommendation for the determination of field capacity is that it must be performed in situ ; however, due to its slow process, the method has been performed in labs. The present work was developed using data available in literature, compiled in such a way to create a database about the subject studied. A comparative analysis between the volumetric humidity values, obtained through field experiments and the volumetric humidity values estimated by the proposed methodology, and also using the different adjustment models of the water retention curve in soil. In order to establish the comparison, a regression analysis between the values of field capacity was performed using the many procedures in attempt to obtain the correlation coefficient (r) and the Wilmont concordance index (c). From the results obtained in this work it is possible to conclude that the evaluation of the proposed methodology the estimative of field capacity concerning an inflection of the retention curve when modeled by a third-degree polynomial presented performance in the class outstanding and very good in 66.5% of the cases and classes of performance very weak 16,6% and extremely bad in about 16,6% of the cases. The applied methodology did not present consistent results for the different sources of data used and in a general way, the best found